Legal Implications For Notary Who Does Not Attach The Fingerchop On Original Agreement - Edi Adi Ambarawa; Yudi Hendarto; Djauhari Djauhari (Jurnal Akta, 2018)
This study aims to find out the background of the attachment of fingerchops to the Original Agreement and legal implications for Notary who do not attach it. This study used the normative legal research method, through the approach of law to gain views and doctrine as the basis of legal argument on legal issues studied. Based on the results, it can be seen that the background attached fingerchop tap on the Original Agreement aims to anticipate when the applicant denied his signature. Thus, as additional evidence uses fingerchops. Legal implications for a Notary who does not attach a fingerchop to the Original Agreement may be subject to sanctions in accordance with Article 16 paragraph (11) of Notary Law: (a) written notice; (b) temporary dismissal; (c) dismissal with respect; (d) dismissal with disrespect. If a written warning sanction to a Notary is not complied with or violated by the Notary concerned, then the following sanctions may be imposed in stages.Keywords: Notary; Fingerchop; Original Agreement.